(untitled) (Research, Society and Development, 2021)
The presence of pathologies in the asphalt pathways generates discomfort and insecurity for its users, making it necessary to identify these pathologies and correct them. The objective of this study is to identify and analyze the main pathologies existing on Avenida Maria Merandoilina, and the impacts caused on this road that connects the Nossa Senhora das Dores and Rendeiras neighborhoods. DNIT’s continuous visual survey method was used to assess the physical quality of the avenue, in order to show its quality classification and which repairs were necessary to restore the quality of the avenue. The road has 118 points of damage and defects of various pathologies along the 1 km analyzed, which classifies the avenue as bad in general. The pathologies that stood out in the analyzed stretch were wear, patches and cracks alligator leather, so that the road needs to be resurfaced with prior corrections, in order to remedy or mitigate the pathologies found and provide quality and safe traffic. According to the normative parameters, the study road requires repairs and care, due to its high pathological degree that compromises its efficient use, in order to safely provide the traffic of cars and pedestrians using the road.